Multigenerational family coaggregation study of obsessive-compulsive disorder and cardiometabolic disorders - David Mataix-Cols; Christian Rück; Lorena Fernández de la Cruz; Kayoko Isomura; Henrik Larsson; Paul Lichtenstein; Brian M D’Onofrio; Anna Sidorchuk; Zheng Chang; James J Crowley; Ralf Kuja-Halkola; Isabell Brikell; et al. (BMJ Mental Health)
Background Obsessive-compulsive disorder (OCD) is associated with an increased risk of morbidity and mortality due to cardiometabolic disorders. Whether this association is driven by familial factors is unknown. This population-based family study explored the familial co-aggregation of OCD and cardiometabolic disorders.Methods We identified 6 049 717 individuals born in Sweden between 1950 and 2008, including 50 212 individuals with OCD, and followed them up to 2020. These individuals were linked to their mothers, fathers, full siblings, maternal and paternal half siblings, aunts, uncles and cousins. We estimated the risk of cardiovascular diseases (CVD) and metabolic disorders (including obesity, type 2 diabetes and hyperlipidaemia), comparing the relatives of probands with and without OCD. Cox proportional hazards regression models, incorporating time-varying exposures, estimated HRs.Results OCD was associated with an increased risk of CVD (HR 1.47; 95% CI 1.43 to 1.51), obesity (HR 1.69; 95% CI 1.63 to 1.74), type 2 diabetes (HR 2.01; 95% CI 1.90 to 2.12) and hyperlipidaemia (HR 1.42; 95% CI 1.33 to 1.52). The relatives of probands with OCD exhibited small increased risks of CVD (HRs from 1.01 to 1.11) and obesity (HRs from 1.03 to 1.20). Slightly increased risks for type 2 diabetes were observed in mothers (HR 1.11; 95% CI 1.07 to 1.15) and full siblings (HR 1.12; 95% CI 1.05 to 1.20), while for hyperlipidaemia it was only observed in mothers (HR 1.06; 95% CI 1.02 to 1.10).Conclusions Our results do not support a major contribution of familial factors to the association between OCD and cardiometabolic disorders, suggesting a more prominent role of unique environmental factors.